Role of regular yoga practice in improvement of various pulmonary parameters in first year medical students - Kumar, Kislay; Kumar, Devesh; Pandey, Pooja T.; ., Divya (International Journal of Research in Medical Sciences, 2018)
Background: tress at any stage of life virtually produces several respiratory limitations and reduces tolerance to physical efforts, sometimes leading to pulmonary diseases in individuals. Various yoga and Pranayama like Kapalbhati and Nadi-sodhan involves powerful strokes of exhalation, which trains the subject to make full use of diaphragm and abdominal muscles. Methods: This study is performed on 1st yr. medical students whose stress level is in higher side due to academic burden. 55 medical students were selected as participants through counseling and were divided into Yoga group (n= 27) and control group (n=28). Pulmonary functions of subjects were tested using Pony FX advanced desktop spirometer manufactured by Cosmed. Yoga is performed 1 hr/day for 6 days /week for 12 weeks by yoga group. Results: Pulmonary functions tested in Yoga and control group were FVC, FEV1, PEF and FVC/FEV1. There were significant improvements in pulmonary functions in yoga group. In Yoga group (FVC- 5.8% increases, FEV1- 5.2% increase, PEF- 34% increase and FVC/FEV1- 3.15% increase). In control group also, all parameters increased but P value was not significant. Conclusions: This study concludes that practicing Yoga has shown a significant improvement on pulmonary functions in 1st year medical students.